ANALISIS SPASIAL PADA PDRB SEKTOR INDUSTRI PENGOLAHAN DI KABUPATEN/KOTA PROVINSI JAWA BARAT - Marnita Simatupang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The Manufacturing Sector is the leading sector in Indonesia's GDP. The provincewith the largest contribution is West Java Province. The manufacturing sectorgenerates as much as 41.9 percent of GRDP in West Java Province. Therefore, theeconomic growth of a region will be related to economic growth in other contiguousareas. The existence of this dependence pattern requires an analysis that considersthe spatial aspects in its calculations. This study uses the Spatial Durbin Model(SDM) method in modeling the GRDP of the Industrial Sector (